Traces of History, Development and Condition Old Banyuwangi Station - Bela Sabela Nina; Abdul Hadi; Marsiyah, Marsiyah; Moh. Chairul Ibad; Wahyu Alfariski; Asil Ainulloh; Diki Maulani (CV. Sekawan Siji, 2024)
The purpose of this research aims to explore the history, development, and condition of Old Banyuwangi Station to the local community. The research method we use in this research is the historical research method. With several data collection techniques including observation, direct interviews with sources who have knowledge and experience about the history of the Old Banyuwangi station, and also with several sources from related scientific articles. The results show that the Old Banyuwangi station has a long historical trail of development from opening to closing the station, and has an impact that changes the lives of the surrounding community. In addition, this research also shows that Old Banyuwangi station has high historical and architectural value, with buildings that still exist today. However, this research also found that Old Banyuwangi station is undergoing changes and needs special attention in its maintenance and preservation. Thus, by conducting this research we hope that this research will contribute to add insight into the history of Old Banyuwangi station from an oral history perspective.